Factores que inciden en el rendimiento académico de matemáticas en octavo y noveno año de la “Unidad Educativa pedro Vicente Maldonado” - Cando Villa, Jennyfer Elizabeth (2023)
Mathematics learning is affected by various factors that are related to the academic performance, these factors can be related positively and negatively, at the same time influence their study habits, self-esteem and practice This research work focuses on the study of the factors that are related to the academic Mathematics performance at the eighth and ninth year students, whose general objective is to determine the factors that are related to the academic performance in Mathematics in the eighth and ninth year students of the Educational Unit "Pedro Vicente Maldonado" in the year 2023. In addition, the theoretical framework addresses academic performance, and the scale managed by the Ministry of Education. A bibliographical review on institutional, pedagogical, socioeconomic, sociocultural, psychological factors and learning styles is also presented. The study is based on a quantitative approach of non-experimental design, applying a survey for data collection. For data processing and statistical analysis, the SPSS tool was obtained. We worked with a sample of 215 students in the eighth and ninth year of EGB. The research hypothesis was to determine if there is a relationship between the pedagogical, institutional, socioeconomic, psychological and sociocultural factors associated with the student and the academic performance of Mathematics in the students of the Educational Unit "Pedro Vicente Maldonado" and by the used of Chi- squared test, it was concluded that, factors such as age, compliance with the established schedule, the level of study reached by the parents and the activities developed by the teacher, are related to academic performance; recommending that the institution, authorities and teachers take the respective actions, in controlling the timing of teachers and compliance with the schedule established during the development of the classes so that it allows to achieve better results at the end of the academic period.